INTELLIGENT MONITORING OF PAPAYA TREES USING IOT-BASED SENSORS - Kumar, Krishan; Yadav, Rakesh K. (International Journal of Research -GRANTHAALAYAH, 2024)
The boom of IoT Technology emphasizes its significance in various applications like Smart Farming and Manufacturing. In India Agriculture is an important sector since it is a major contributor to the Nation’s economy. In India, there are certain factors as hurdles to growing well in agriculture. The aim of this work is to employ smart farming of Papaya Trees using IoT. This smart system monitors the growth of the Papaya tree as well as the weather conditions like moisture, humidity, and temperature through sensors. The main component of this proposed system is to control the watering of crops using mobile application with a help of smartphone. This paper also discusses the design and development of the system which uses sensors in the crop field and the data administration using smartphone and web technology. This will reduce human intervention and increase the productivity of the crop.